Societal preferences for funding orphan drugs in China: An application of the discrete choice experiment method - Tan, Shuoyuan; Wang, Yu; Tang, Yuqing; Jiang, Rong; Chen, Mingsheng; Chen, Haihong; Yang, Fan (Frontiers in Public Health, 2022)
Objectives: To explore whether a societal preference for orphan drugs exists in Chinese general public and to quantitatively measure the personal trade-off between essential attributes of orphan drugs through a discrete choice experiment. Methods: A labeled discrete choice experiment was employed to measure public preference. Six attributes (impact of diseases on life-years, impact of diseases on quality of life, availability of alternative drug treatments, annual cost per patient paid by medical insurance, expected increase in life-expectancy, and improvements to the quality of life) were identified through a literature review, experts’ suggestions, and stakeholders' semi-structured interviews, then refined through a pre-survey. The current study used a D-efficient design to yield 27 choice sets divided into 3 blocks with 9 questions containing the labeled treatment (either orphan drugs or common drugs). Information on sociodemographic characteristics and individual preferences was collected through a web-based questionnaire using convenience sampling. A mixed logit model was used to test societal preferences for orphan drugs over common drugs, while a binary logit model was used to measure the relative importance of each attribute in orphan drug access for the National Reimbursement Drug List and its willingness to pay. Results: A total of 323 persons participated in this study. Respondents largely had indifferent attitudes toward orphan drugs and common drugs. The binary logit model results showed that 5 of the 6 attributes were significant, except for the availability of alternative drug treatments. The most impacted factor was the annual cost per patient paid by medical insurance (β = −1.734, odds ratio [OR] = 0.177). Among non-economic attributes, the impact of diseases on life-years—with no treatment, the patient will die in the prime of life (β = 0.523, OR = 1.688, willingness to pay = 301,895)—was most concerning, followed by significant improvements to the quality of life (β = 0.516, OR = 1.676, willingness to pay = 297,773). Conclusions: The general public in China does not value rarity as a sufficient reason to justify special consideration in funding orphan drugs. When making orphan drug coverage decisions, the public prioritized the annual cost, disease severity, and drug effects.